2011
DOI: 10.1111/j.1469-8986.2010.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Interhemispheric ERP asymmetries over inferior parietal cortex reveal differential visual working memory maintenance for fearful versus neutral facial identities

Abstract: The goal of the present investigation was to discover whether visual working memory maintenance for faces is modulated by facial expression using event-related potentials (ERPs). Each trial consisted of two sequential arrays, a memory array and a test array, each including either two or four faces with neutral or fearful expressions. The faces were displayed to the left and to the right of a central fixation cross. Two central arrows cued participants to encode one face or two faces displayed on one side of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(114 citation statements)
references
References 88 publications
11
97
5
1
Order By: Relevance
“…Indeed, even if external threat cues predominantly impaired visual memory performance (in the case of low anxious individuals), this also discords from evidence that threat signals generally should improve early information processing and sensory acquisition (Phelps et al, 2006), which we hypothesised might translate to greater visual memory performance as when emotional information itself is maintained (Sessa et al, 2011). This can be reconciled within the present study, if one assumes that the influence of external threat on sensory processing does not extend beyond initial perception to the level of visual memory performance.…”
Section: Visual Memory Performancementioning
confidence: 60%
See 3 more Smart Citations
“…Indeed, even if external threat cues predominantly impaired visual memory performance (in the case of low anxious individuals), this also discords from evidence that threat signals generally should improve early information processing and sensory acquisition (Phelps et al, 2006), which we hypothesised might translate to greater visual memory performance as when emotional information itself is maintained (Sessa et al, 2011). This can be reconciled within the present study, if one assumes that the influence of external threat on sensory processing does not extend beyond initial perception to the level of visual memory performance.…”
Section: Visual Memory Performancementioning
confidence: 60%
“…This can be reconciled within the present study, if one assumes that the influence of external threat on sensory processing does not extend beyond initial perception to the level of visual memory performance. Indeed, whereas Sessa et al (2011) found strong evidence of improved maintenance, this may be due to the emotional information itself being memorised. In our study, emotion was incidental to the task, and so external threat exposure may only beneficially impact visual working memory when emotional material itself is maintained.…”
Section: Visual Memory Performancementioning
confidence: 97%
See 2 more Smart Citations
“…A lateralized change detection working memory task, adapted from prior event-related potential (ERP) research by our group (Stout et al, 2013) and others (Sessa, Luria, Gotler, Jolicœur, & Dell'Acqua, 2011), enabled us to estimate the number of threat-related and emotionally-neutral faces stored in working memory (See Figure 1). This design enabled direct comparison with prior ERP research (e.g., Stout et al, 2013).…”
Section: Methodsmentioning
confidence: 99%